Quality of Life with Workplace Spirituality: The Context of University Personnel in Thailand - teeratanatorn, naratip; Bureerat, Thanawat (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2021)
The influence of surrounding factors leads to adaptation of universities in Thailand to comply with changes these days. These circumstances unavoidably affect university personnel which result in more stress and pressure. This article aims to propose the concept of workplace spirituality. This concept supports university personnel to be aware of the value and the heart and soul of themselves which boosted by valued and meaningful work. Workplace spirituality can be conceptualized as a desire to have relationships with others in the organization and being a team with the same goal. Workplace spirituality is related to quality of life which is important that an organization must support its personnel to have good quality of life. The guidelines for life quality development to enhance workplace spirituality of Thai university personnel are divided into four dimensions. For working dimension, the personnel’s workload should be determined to be suitable for their manpower, tasks should be assigned according to the capabilities of the personnel, and the works at all levels should be valued. For social dimension, there should be the development of relationships between personnel, promoting the channels for personnel to exchange and learn useful things to support each other, and encouraging personnel to appreciate themselves and others. The next one is economic dimension which is an important factor that should be adequately and appropriately promoted to achieve a healthy condition in order to reduce worries that bothers them in working. The last one is personal dimension which should develop the management of proper working time, encourage personnel to do activities that build relationships with their family members, as well as building a bond with the external society to create a balance in the personal dimension of university personnel in Thailand.